Social innovation and rural territories: Exploring invisible contexts and actors in Portugal and India - Ferreiro, M. F. (2022)
Social innovation has come to be identified as a key aspect of development. Objectives related to personal and socioeconomic development often inspire this type of innovation. Relevant goals can drive societies to fulfil citizens’ needs while promoting overall empowerment and inclusion. This paper analyses the emergence and development of social innovation in rural territories in the opposing socioeconomic settings of Portugal and India. By addressing social innovation in rural territories, the paper contributes to the research and provides empirical evidence from contexts and analytical frameworks that have been neglected by most innovation scholars. The paper acknowledges the context of innovation processes and dynamics - rural territories in western and non-western countries. The consideration of two different, contrasting socioeconomic contexts provides a privileged framework to analyse the dynamics involved in the emergence and development of social innovation, namely the top-down and bottom-up approaches that characterize it.